Pengaruh Profitabilitas Terhadap Agresivitas Pajak: Studi Pada Perusahaan Manufaktur Di Bursa Efek Asean - Crissyen Deara Ellysta (Jurnal Literasi Akuntansi, 2024)
Purpose: This study aims to examine the influence of profitability on tax aggressiveness among manufacturing companies listed on the ASEAN stock exchange from 2018 to 2023. Method: A quantitative research method is employed, using a sample of manufacturing companies listed on the ASEAN stock exchange. Finding: The results show that profitability, measured by Return on Assets (ROA), has a negative impact on tax aggressiveness. This means that companies with high ROA tend to better fulfill their tax obligations and conduct good tax planning. This study contributes to the understanding of factors influencing tax aggressiveness and its implications for financial management and corporate transparency. Novelty: This study provides new contributions to the study of tax aggressiveness by expanding the geographical scope by using ASEAN manufacturing company data, updating the data, and confirming the negative relationship between profitability and tax aggressiveness.